Cybersecurity Risks in a Pandemic - Williams, Christina Meilee; Chaturvedi, Rahul; Chakravarthy, Krishnan (JMIR Publications, 2020)
Cybersecurity threats are estimated to cost the world US $6 trillion a year by 2021, and the number of attacks has increased five-fold after COVID-19. Although there is substantial literature on the threats technological vulnerabilities have on the health care industry, less research exists on how pandemics like COVID-19 are opportunistic for cybercriminals. This paper outlines why cyberattacks have been particularly problematic during COVID-19 and ways that health care industries can better protect patient data. The Office for Civil Rights has loosened enforcement of the Health Insurance Portability and Accountability Act, which, although useful in using new platforms like Zoom, has also loosened physical and technical safeguards to cyberattacks. This is especially problematic given that 90% of health care providers had already encountered data breaches. Companies must implement well-defined software upgrade procedures, should use secure networks like virtual local area networks, and conduct regular penetration tests of their systems. By understanding factors that make individuals, health care organizations, and employers more susceptible to cyberattacks, we can better prepare for the next pandemic.